RANK is essential for osteoclast and lymph node development - Dougall, William C. (Cold Spring Harbor Laboratory Press, 1999)
The physiological role of the TNF receptor (TNFR) family member, RANK, was investigated by generating RANK-deficient mice. RANK(−/−) mice were characterized by profound osteopetrosis resulting from an apparent block in osteoclast differentiation. RANK expression was not required for the commitment, differentiation, and functional maturation of macrophages and dendritic cells from their myeloid precursors but provided a necessary and specific signal for the differentiation of myeloid-derived osteoclasts. RANK(−/−) mice also exhibited a marked deficiency of B cells in the spleen. RANK(−/−) mice retained mucosal-associated lymphoid tissues including Peyer’s patches but completely lacked all other peripheral lymph nodes, highlighting an additional major role for RANK in lymph node formation. These experiments reveal that RANK provides critical signals necessary for lymph node organogenesis and osteoclast differentiation.